2007
DOI: 10.1159/000105320
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Correlates of the Treadmill Scores in Non-High-Risk Patients with Unstable Angina

Abstract: Background: There has been no clear consensus regarding the optimum definition of a high-risk exercise ECG test. The aim of this study is to compare the diagnostic accuracy of several treadmill scores [American College of Cardiology/American Heart Association (ACC/AHA) High-Risk Criteria for exercise testing, Duke Treadmill Score, Veterans Affairs and West Virginia Prognostic Score, ST/Heart Rate Index] with the ST-segment depression analysis in the detection of significant and severe coronary disease as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Regarding the accuracy of the various diagnostic strategies examined for identifying CAD, Khare et al. rely on high‐quality meta‐analyses . Khare et al.…”
Section: Was the Effectiveness Of The Healthcare Decision Established?mentioning
confidence: 99%
“…Regarding the accuracy of the various diagnostic strategies examined for identifying CAD, Khare et al. rely on high‐quality meta‐analyses . Khare et al.…”
Section: Was the Effectiveness Of The Healthcare Decision Established?mentioning
confidence: 99%
“…However, only a small number of patients, in total of 562, were studied. Barriales et al studied only 300 patients and found that DM was an independent risk factor for atrial fibrillation (10). In the International Journal of Cardiology Mohaved et al retrospectively analysed discharge diagnoses and concluded that diabetes mellitus was a strong and independent risk factor for occurrence of AF.…”
Section: Diabetes Mellitusand Atrial Fibrillationmentioning
confidence: 99%